The tragic route of Baron Tiesenhausen - S. A. Papkov (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to D. O. Tiesenhausen, a descendant of an old Russian noble family. Describes the main stages of the career and life of the baron as vice-governor of the Orenburg and Vyatka provinces and Yakutsk region. His ideological positions regarding the February Revolution of 1917 and political exile to Yakutia are presented. On the basis of new sources analyzed one of the most dramatic periods of the biography of the Baron, associated with his emigration to Mongolia, stay in Urga and relations with General Ungern. A separate episode in the life of the former Vice-Governor was his arrest, transportation to Siberia and imprisonment in a detention center. This arrest nearly resulted in the death penalty by decision of the Irkutsk provincial police. The Baron spent the rest of his life under the systematic control of the Stalinist secret services, and his personal tragedy was a typical expression of the fate of most «socially alien» people in Soviet Russia.